Compensation Anomalies and Contextual Performance: The Moderating Role of Public Service Motivation Among Part-Time Employees - Shoalihin; Firmansyah (Yayasan Sinergi Kawula Muda, 2026)
This study aims to examine and analyze the effect of compensation anomalies on contextual performance, as well as to explore the role of public service motivation as a moderating variable among part-time government employees in Dompu Regency. Compensation anomalies in this study are conceptualized as systemic deviations of a structural nature, encompassing uncertainty regarding payment schedules, ambiguity in wage regulations, and discrepancies between actual workloads and administrative legalities frequently experienced by contract employees. The study population consisted of 5,387 part-time employees (honorary staff), with a sample of 373 respondents. Primary data were collected via a questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS 3.0 software. The results of the data analysis indicate that compensation anomalies have a positive and significant effect on both contextual performance and motivation in public service. Theoretically, this finding is counterintuitive because financial uncertainty, which typically reduces performance, actually fosters a sense of shared adversity among employees in this study. Furthermore, Public Service Motivation (PSM) was found to have a positive effect on contextual performance and acts as a moderating variable that mitigates the impact of this anomaly. PSM functions as a psychological anchor that neutralizes compensation distortions through the idealism of public service. However, these findings must be interpreted cautiously as a reflection of a specific local sociocultural context; thus, their practical implications cannot be generalized to justify anomalous compensation systems in other regions.